Social Presence within the Community of Inquiry Framework - Annand, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The role of social presence as defined by the community of inquiry (CoI) framework is critiqued through a review of recent literature. Evidence is presented that questions the actual extent of knowledge co-construction that occurs in most higher education settings and therefore challenges the framework’s underlying assumption of the need for sustained, contiguous, two-way communication in higher-level online learning environments. The CoI framework has evolved from the description of a learning process within a social constructivist paradigm to an empirically testable construct in an objectivist paradigm. Related research results indicate that social presence does not impact cognitive presence in a meaningful way and that best teaching practices suggested by CoI-based studies are informed by objectivist, cognitively oriented learning theories. These suggest that higher-order cognition may be achieved through wide and varied combinations of learner–teacher, learner–content, and learner–learner interaction. Controlled studies can and should be undertaken to compare learning outcomes using sustained, contiguous, two-way communication to other learning models. To facilitate this, subcategories of social and teaching presences need to be revamped and analysis adjusted to separate processes that support explicitly group-based learning activities from those used by individual students.